Absorbing properties of metamaterial dihedral corner reflector - Taoming Lu; Youcheng Wang; Helin Yang; Xiaojun Huang; Yanfei Zhou; Jiong Wu (Materials Research Express, 2020)
In this paper, the absorbing property of metal-cross shaped metamaterial dihedral (MCMD) and cross-cross shaped metamaterial dihedral (CCMD) with the same parameters are investigated. In TE mode, the absorptivities are 91.1% at 9.17 GHz for MCMD and 99.7% at 9.20 GHz for CCMD. For MCMD and CCMD, the absorptivities are 90.5% and 99.8% at 9.2 and 9.17 GHz respectively for the TM polarized incident wave. The results of simulation and measurement show that CCMD has better multi-band absorption performance and lower radar cross-section than MCMD. Experiments have demonstrated the reflection coefficient can be utilized to analyze the electromagnetic characteristics of dihedral corner as well. The study of dihedral corner reflector is of great importance as it is used in modeling many areas such as stealth technology, electromagnetic compatibility and target recognition.